Informal Coercion Experienced by Adolescents in Mental Health Care—A Systematic Review - Överlund, Tiina; Lantta, Tella (Wiley, 2026)
Adolescents are a developmentally vulnerable group in mental health care, yet their experiences of informal coercion remain underexplored. Most existing research reflects adult perspectives, leaving a gap in understanding how adolescents experience such practices. This review synthesises qualitative evidence on the forms and consequences of informal coercion experienced by adolescents in mental health settings. The review followed the PRISMA guidelines and was registered in PROSPERO. A systematic search was conducted across seven databases in February 2025 (PubMed, CINAHL, PsycINFO, EMBASE, Scopus, Web of Science, Cochrane Library). Screening and inclusion were performed using Covidence supplemented by manual reference searches. Qualitative content analysis was applied, using a framework informed by previously identified forms of informal coercion. Across 12 studies, informal coercion shaped adolescents' involvement in mental health care. Predominant forms included treatment pressure, silencing and exclusion and appealing to rules and routines, accompanied by threats or disciplinary control. These practices were experienced as undermining autonomy and trust. The adolescents responded through adaptive and resistant coping strategies, such as compliance, concealment, or overt opposition. The experiences were commonly associated with emotional distress, relational mistrust and hindered recovery, although some adolescents interpreted structured pressure as supportive or protective. Informal coercion is present and consequential in adolescent mental health care. Existing adult-based conceptualisations may overlook its relational and subtle nature. Further research is needed to explain how informal coercion is constructed in interactions and how it is justified in adolescent mental health care. Such knowledge is essential for developing ethically sound, rights-respecting nursing practices.